Cameroon Refugees’ Settlement in Ogoja, Nigeria: Implication on Labour Market and the Environment - A., Edem Ebong; Ogaboh, Agba, A.; Eru, Iji, M. (Global Journal of Social Sciences Studies, 2020)
This study examined the impact of Cameroon refugees’ resettlement on labour market and the environment of Ogoja Local Government Area of Cross River State, Nigeria. Two objectives and hypotheses were raised for the study. Descriptive survey design was used which allows for purposive and simple random sampling of 384 participants from Cameroon refugee camp in Ogoja and its environs. Elicited data were analyzed using Lineal Regression. Results revealed that the camping of Cameroon refugees has significantly altered the dynamics of the labour market in Ogoja Local Government Area. Results also publicized the negative effect of refugee settlement on sanitation and ecology of Ogoja Local Government Area. Based on these findings, the study recommended among others that the Cross River State Government, the Federal Government and other aid agencies should provide jobs and livelihood programmes that will help refugees achieve self-reliance, good sanitary condition and boost the economy of Ogoja Local Government Area.